KONTRIBUSI NORMATIF ABU HANIFAH DALAM PENENTUAN AWAL BULAN KAMARIAH - Fatmawati, Emyllia; Syarif, Rasdiyanah Audiah (ELFALAKY: Jurnal Ilmu Falak, 2021)
This research is seen from Muslims who are faced with the problem of determining the beginning of the month of Kamariyah, but they still have not found a common point, as is the difference in the opinions of the scholars of the four schools regarding the determination of the beginning of the month of Kamariyah. In Islam, the determination of the beginning of the lunar month begins with the sight of the new moon, which is part of ijtihad. Abu Hanifah is one of the imam of the madzab who made a valuable contribution to the development of Islamic law. His Ijtihad about fulfilling 30 days when cloudy in determining the beginning of the month of kamariyah has been used by the followers of this madzab, which is only 30% in the world such as in India and Pakistan and Afghanistan. The purpose of this research is to study the method used by Imam Hanafi, one of the four Imam Madzab in determining the beginning of the month of the month.